The Ionospheric Dynamics of the African Sector Responding to a Severe Geomagnetic Storm; the Storm of 3–5 November 2021 - Wellen Rukundo (Space Weather)
Abstract The sudden storm commencement (SSC) of 3 November 2021, a severe storm was detected through disturbances in magnetospheric and ring current systems at around 1942 UT. We used a daily variation of total electron content (TEC) from ground‐based GNSS stations, ionosonde parameters and modeled zonal and meridional wind velocities to study the ionospheric response over the African region by comparing storm and quiet time variations. The equatorial GNSS station of NKLG recorded initial positive storm effects around the time of SSC, of which these effects spread over the whole African region during the main phase with positive and negative storm effects during the main and recovery phases respectively. The two disturbances at the SSC and the main phase were caused by the penetrating electric field and traveling atmospheric disturbances respectively. The analysis of TIMED Global UltraViolet Imager images revealed storm time‐induced changes in thermospheric composition during the main phase which resulted in a differential ionospheric response with intense, moderate, and weak positive storm effects in northern, equatorial, and southern regions respectively. The horizontal magnetic field components show two signatures of prompt penetration electric field that suppressed the formation of the equatorial anomaly at SSC and enhanced positive storm effects in the equatorial region at the main phase, Therefore, the ionospheric response was due to the relative contributions of prompt penetration electric field effects and equatorward traveling disturbances which depended on storm onset time, past ionospheric state, and storm phase.